The use of gambir as coloring agent in dyeing of cotton textile (Balai Riset dan Standardisasi Industri Palembang, 2011)
The objective of this research was to study the use of gambir as coloring agent on cotton fabric by using specific dipping condition and to obtain the best gambir concentration. Concentrations of gambir solution used in this study were 7.5, 12.5, 17.5, and 22.5 g/l, respectively. Dipping process was started by soaking of cotton fabric in gambir solution for 15 minutes at 40–100 °C temperature which was subsequently dried and put in room temperature for 15 minutes. The fixation process was repeated seven times using 5% weight/volume of calcium hydroxide for 15 minutes. The results showed that grey scale for colorfastness was in the range of 1 to 3. Coloring scale in cotton fabric was in the range of3.5 to 4.5 and it was 4 to 5 on polyesther fabric. Coloring scale on dry ironing was in the range of 4 to 5 and it was 2.5 to 4 on wet ironing. The L* value was in the range of 40.5 to 64.84, a* value was in the range of 10.71 to 19.76 and b* value was in the range of 16.99 to 24.51. The best concentration of gambir solution was 2.5% with L* value of 64.84, * value of 12.04 and b* value of 17.38. The grey scale was 3, coloring scale on cotton and polyesther fabrics was 5, coloring scale for dry ironing was 5 and coloring scale for wet ironing was 4.Keywords: Gambir, coloring agent, cotton fabric, coloring scale, concentration AbstrakPenelitian ini bertujuan untuk mempelajari penggunaan gambir sebagai bahan pewarna pada kain kapas dengan kondisi percelupan tertentu dan mendapatkan konsentrasi gambir yang terbaik. Konsentrasi larutan gambir yang digunakan adalah 7,5; 12,5; 17,5; 22,5 (g/l). Proses pencelupan dimulai dengan perendaman kain kapas dalam larutan gambir selama 15 menit, suhu di 40–100 °C, kemudian dikeringkan dan diletakkan pada suhu kamar selama 10 menit. Proses pengulangan fiksasi sampai tujuh kali dengan 5% b/v kalsium hidroksida selama 15 menit. Hasil penelitian menunjukkan bahwa skala abuabu untuk color fastness berkisar antara 1–3. Skala pewarnaan pada kapas berkisar antara 3,5–4,5, sedangkan pada poliester berkisar antara 4–5. Pewarnaan skala untuk menggosok kering berkisar 4–5; untuk menggosok basah berkisar antara 2,5–4. Nilai L* berkisar antara 40,5–64,84, nilai a* berkisar antara 10,71–19,76, dan nilai b* berkisar antara 16,99–24,51. Konsentrasi terbaik larutan gambir adalah 2,5% dengan nilai L* adalah 64,84, nilai a* adalah 12,04; b* adalah 17,38. Skala Grey adalah 3. Skala pewarnaan pada kapas dan polyester adalah 5. Skala Pewarnaan dalam menggosok kering adalah 5, dan menggosok basah adalah 4.Kata Kunci: gambir, pewarna, kain kapas, skala pewarnaan, konsentrasi